Investigation of the effects of Pr doping on the structural properties of hydroxyapatite: an experimental and theoretical study - Agid, Riyadh Saeed; Kaygili, Omer; Bulut, Niyazi; Dorozhkin, Sergey, V; Ates, Tankut; Koytepe, Suleyman; Mahmood, Bahroz Kareem (Springer, 2020)
Five samples of hydroxyapatite (HAp) doped with praseodymium (Pr) at various amounts (2, 4, 6, 8, and 10 at.%) were synthesized by using the wet chemical route. The effects of Pr doping on the structural and thermal properties, as well as on the in vitro performance of HAp, were investigated experimentally. The band structure and density of states (DOS) of HAp were studied theoretically. Incorporation of Pr into the crystal lattice of HAp was observed. A gradual increase in the crystallite size, lattice parametera, and unit cell volume was found, and a gradual decrease in the crystallinity degree was seen. Pr content from 2 to 10 at.% did not affect the thermal stability of HAp. The theoretical results showed that the bandgap energy of HAp decreased steadily from 3.82 to 1.32 eV with the adding of Pr, and the DOS was also affected by the Pr content. The cell viability tests showed that among all the as-synthesized samples, the best biocompatible properties were found for the sample which was doped with 10 at.% Pr, and the amount of Pr affected significantly the cell viability property of HAp. Except for the sample having 6 at.% Pr, all the remaining samples appeared to be potentially good candidates for biomedical applications.
Keywords: Praseodymium; Hydroxyapatite; Wet chemical method; X-ray diffraction (XRD); Band structure